Creating an Inclusive Educational Environment for Children with Special Educational Needs (Texas Journal of Engineering and Technology, 2023)
The article discusses the issue of the conditions for providing accessible education for children with special educational needs, the development of special education in Uzbekistan and its situation at this stage of development